Metal imidazolate sulphate frameworks as a variation of zeolitic imidazolate frameworks. Issue 18 (11th February 2022) - Noh, Kyungkyou; Sim, Jaeung; Kim, Jonghoon; Kim, Jaheon
Abstract : Both imidazolate and sulphate ions can connect metal ions to give extended structures resembling zeolitic imidazolate frameworks. Abstract : Sulphate ions can be incorporated into zinc imidazolate frameworks to give rise to zinc imidazolate sulphate frameworks, that is, a square-grid network, a zeolite-like GIS framework, or a porous pillar-layered structure where interlayer octahedral Zn 2+ ions connect honeycomb-like layers.